Alveolar Ridge Preservation with Autologous Platelet-Rich Fibrin (PRF): Case Reports and the Rationale - Cemal Ucer; Rabia S. Khan (MDPI AG, 2023)
In dental implantology, alveolar ridge preservation (ARP) has emerged as a standard technique to address dimensional changes that affect alveolar ridge morphology following tooth loss. Various alternative graft materials, including xenografts, alloplasts, and allografts, have been effectively employed in fresh extraction sites for ARP. Current evidence suggests that these materials primarily serve as bio-scaffolds, which are slowly incorporated, thus necessitating a waiting period of at least 4-6 months before implant placement. Consequently, the ARP technique extends the overall duration of implant treatment by several months. Recently, the incorporation of a form of autologous platelet concentrate, known as platelet-rich fibrin (PRF), has been advocated in conjunction with ARP as a method of bioenhancement of soft- and hard-tissue healing and regeneration. PRF contains platelet-derived growth factors, hormones, and bioactive components like cytokines that have demonstrated the ability to stimulate angiogenesis and tissue regeneration throughout all phases of wound healing. Additionally, the concentration of leukocytes present in the PRF matrix plays a vital role in tissue healing and regeneration as part of the osteoimmune response. The reported advantages of incorporating autogenous PRF platelet concentrates during ARP encompass reduced healing time, improved angiogenesis and bone regeneration, socket sealing through the fibrin matrix, antibacterial properties, and decreased post-extraction pain and infection risk. Therefore, the objective of this paper is to review the existing evidence regarding the application of PRF in alveolar ridge preservation (ARP) following tooth extraction. Two clinical case studies are presented, wherein ARP was enhanced with PRF, followed by implant placement within a relatively short period of 8 weeks. These cases serve as further proof of concept for supporting the adjuvant use of PRF to enhance healing and accelerate implant placement after ARP.